2003
DOI: 10.1002/ffj.1228
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the aroma impact compounds in heated sweet cream butter

Abstract: This study was conducted to determine which volatile compounds are primarily responsible for the aroma of heated sweet cream butter. Static headspace analysis was used for aroma isolation and gas chromatography–olfactometry (GC–O) for the selection of odour‐active components. Quantification of selected odourants was done via purge and trap‐GC/mass spectrometry (MS). Nineteen odour‐active compounds were detected in the headspace (static) of heated butter (hydrogen sulphide, methanethiol, acetaldehyde, 2,3‐butane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 13 publications
6
17
1
Order By: Relevance
“…The major compounds in terms of concentration were certain lactones, hexanoic acid, butanoic acid, nonanal, hexanal and dimethyl sulphide for the fresh butter [22]. In the heated butter, higher concentrations were determined for lactones, 2-heptanone, butanoic acid, nonanal, (E)-2-nonenal and 3-methylbutanoic acid [23]. When comparing the predominant ions determined in the present study with the volatile compositions of butter and butter oil published, fragmentation patterns need to be considered as well [15].…”
Section: Ptr-ms Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…The major compounds in terms of concentration were certain lactones, hexanoic acid, butanoic acid, nonanal, hexanal and dimethyl sulphide for the fresh butter [22]. In the heated butter, higher concentrations were determined for lactones, 2-heptanone, butanoic acid, nonanal, (E)-2-nonenal and 3-methylbutanoic acid [23]. When comparing the predominant ions determined in the present study with the volatile compositions of butter and butter oil published, fragmentation patterns need to be considered as well [15].…”
Section: Ptr-ms Analysismentioning
confidence: 94%
“…Headspace analysis provides a more representative view of the volatiles that are available for olfactory perception. More recently, Peterson and Reineccius determined the volatile compounds, which are primarily responsible for the aroma of fresh and heated sweet cream butter [22,23] using headspace analysis in combination with gas chromatography-olfactometry. A total of 20 odour active compounds were detected in the headspace of fresh butter and 19 in the headspace of heated butter.…”
Section: Ptr-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…TL-IM and Lipozyme-435 produced more decanoic and dodecanoic acids compared to the amounts produced by Novozyme-435. Decanoic and dodecanoic acids are well known for their contribution to characteristic aroma (Peterson, and Reineccius 2003). Ha and Lindsay (1993) found that pregastric lipase had an ability to release high concentrations of octanoic and decanoic acids from caprine milk; hence both TL-IM and Lipozyme-435 are comparable with pregastric lipase in producing these two flavouring compounds.…”
Section: Spme-gc/ms Analysis Of Volatile Compoundsmentioning
confidence: 99%
“…Butter is widely used as a seasoning in cooking, suggesting that it plays an important role in the formation of flavors during heating (Peterson and Reineccius, 2003;Ito et al, 2005). Besides fats, butter contains small percentages of proteins, milk sugar and water which make it a suitable substrate for microorganisms (Catsberg and Kempen-van Dommelen, 1990).…”
Section: Introductionmentioning
confidence: 99%